Responsibility of PPAT for Differences in Transaction Value with Written Price - Acika Permatasari; Gunarto Gunarto; Widhi Handoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to analyze the factors/reasons, legal consequences and PPAT's responsibility for the difference between the transaction value and the price written on the sale and purchase agreement. This research is included in sociological juridical research with descriptive analysis research specifications. Sources of data used are primary data and secondary data. The data collection was carried out by field research and library research, then after the data was analyzed, conclusions were drawn using qualitative methods. Based on the results of the study, it was found that there was a difference in the transaction value in the sale and purchase deed with the price written on the sale and purchase binding deed, namely the parties avoided high taxes. The legal consequences of PPAT related to the difference in transaction value are that the deed is null and void, the deed is degraded to a private deed and can be dishonorably dismissed from its position. PPAT responsibilities related to deeds include administrative responsibility, civil liability, and criminal responsibility.